Heregulin (HRG) assessment for clinical trial eligibility testing in a molecular registry (PRAEGNANT) in Germany - Hübner, Hanna; Kurbacher, Christian M.; Kuesters, Geoffrey; Hartkopf, Andreas D.; Lux, Michael P.; Huober, Jens; Volz, Bernhard; Taran, Florin-Andrei; Overkamp, Friedrich; Tesch, Hans; Häberle, Lothar; Lüftner, Diana; et al. (BMC cancer, 2020)
Eligibility criteria are a critical part of clinical trials, as they define the patient population under investigation. Besides certain patient characteristics, clinical trials often include biomarker testing for eligibility. However, patient-identification mostly relies on the trial site itself and is often a time-consuming procedure, which could result in missing out on potentially eligible patients. Pre-selection of those patients using a registry could facilitate the process of eligibility testing and increase the number of identified patients. One aim with the PRAEGNANT registry (NCT02338167) is to identify patients for therapies based on clinical and molecular data. Here, we report eligibility testing for the SHERBOC trial using the German PRAEGNANT registry.
Gesehen am 08.02.2021